Legal reasonings of religious court judges in deciding the origin of children: a study on the protection of biological children’s civil rights - Rohmawati Rohmawati; Ahmad Rofiq (State Institute of Islamic Studies (IAIN) Salatiga, 2021)
This study explores the extent to which religious court judges decided the origin of biological children following the implementation of the Indonesian Constitutional Court Decree number 46/PUU-VIII/2010. A substantial ambiguity was apparent in the Indonesian family law concerning civil relationships between children born out of wedlock and their biological fathers. Consequently, judges had different legal interpretations over status of children, which created disparities of the children’s civil right protection. This study focuses on investigating the judges’ legal reasonings when deciding origin of biological children born out of wedlock. This is a case study with a legal philosophical approach. Data collection includes document collection, whereas data analysis involves deductive and inductive approaches. This study found three typologies of judges’ legal reasonings in relation to how they decided the origin of the biological children. Pragmatic judges would not provide legal protection to the biological children as they failed to accept lineage of these children towards their parents, creating uncertainty over the children’s legal status. Conservative judges with a positivistic mindset would acknowledge legal relationship between the biological children and their mothers, generating the children’s civil rights in relation to their mothers. Progressive judges would provide legal protection to the biological children. Progressive judges accepted the lineage of these children towards their parents but acknowledged their civil rights in relation to their fathers in limited ways such as living allowance and testament. Disparities of judges’ decisions regarding the origin of the biological children substantially created a legal uncertainty to these children.